Inovasi Produk Olahan Tahu dan Pengemasannya serta Pengembangan Pemasaran dalam Upaya Meningkatkan Pendapatan Perajin Tahu di Desa Karanganyar Kecamatan Wates Kabupaten Kediri: Innovation in Processed Tofu Products and Their Packaging and Marketing Development in an Effort to Increase the Income of Tofu Crafters in Karanganyar Village, Wates District, Kediri Regency - Purwanto, Bambang Tri; Ekowati, Juni; Widiandani, Tri; Hariyadi, Dewi Melany; Hendradi, Esti; Yusuf, Helmy; Purnomo, Ahmad Toto; Ramadhani, Firmansyah Ardian; Siswandono, Siswandono; Wiyono, Anang Setyo; Yuliati, Ninis; Kristianingsih, Ida; Savitri, Orchidea Meidy Nurintan; Maulia, Arwinda; Rahman, Ave (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
MSMEs in the food sector are among the main supporters of Indonesia's economic activities. As a food production center in the form of tofu products, Kediri Regency is well known to the public, with white, yellow, silk, and other tofu products. Most of the tofu production carried out to date is only in the form of tofu products in their original form. This is because tofu craftsmen have not utilized other processed tofu products to increase their income. This community service activity aims to introduce innovations in processed tofu products, packaging, marketing, and processing of liquid tofu waste into new products which are expected to increase the income of tofu makers in Karanganyar village, Wates District, Kediri Regency. This community service activity was carried out using the media of presenting several materials and carrying out two-way interactive discussions. Evaluation of this activity was carried out with pre- and post-tests from the participants by answering 10 questions related to the three materials. The results obtained after being analyzed using the SPSS program showed differences between the pre-and post-tests of the participants, whereas the post-test results showed that the participants had understood the material provided during this activity. Thus, it can be concluded that this activity can be proven to be understood by the participants regarding innovation in processed tofu products and processing of tofu liquid waste.